Enhancing Palliative Care for Patients With Advanced Heart Failure Through Simple Prognostication Tools: A Comparison of the Surprise Question, the Number of Previous Heart Failure Hospitalizations, and the Seattle Heart Failure Model for Predicting 1-Year Survival - Blum, Moritz; Gelfman, Laura P.; McKendrick, Karen; Pinney, Sean P.; Goldstein, Nathan E. (Frontiers in Cardiovascular Medicine, 2022)
Background: Score-based survival prediction in patients with advanced heart failure (HF) is complicated. Easy-to-use prognostication tools could inform clinical decision-making and palliative care delivery. Objective: To compare the prognostic utility of the Seattle HF model (SHFM), the surprise question (SQ) and the number of HF hospitalizations (NoH) within the last 12 months for predicting one-year survival in patients with advanced HF. Methods: We retrospectively analyzed data from a cluster-randomized controlled trial of advanced HF patients, predominantly with reduced ejection fraction. Primary outcome was the prognostic discrimination of SHFM, SQ (“Would you be surprised if this patient were to die within one year?”) answered by HF cardiologists, and NoH, assessed by receiver operating characteristic (ROC) curve analysis. Optimal cut-offs were calculated using Youden’s index (SHFM: <86% predicted one-year survival; NoH ≥2). Results: Of 535 subjects, 82 (15.3%) had died after one-year of follow-up. SHFM, SQ and NoH yielded a similar area under the ROC curve (SHFM: 0.65 [0.60-0.71 95%CI]; SQ: 0.58 [0.54-0.63 95% CI]; NoH: 0.56 [0.50-0.62 95% CI] and similar sensitivity (SHFM: 0.76 [0.65-0.84 95% CI]; SQ: 0.84 [0.74-0.91 95% CI]; NoH: 0.56 [0.45-0.67 95% CI]). As compared to SHFM, SQ had lower specificity (SQ: 0.33 [0.28-0.37 95% CI] vs. SHFM: 0.55 [0.50-0.60 95% CI] while NoH had similar specificity (0.56 [0.51-0.61 95% CI]). SQ combined with NoH showed significantly higher specificity (0.68 [0.64-0.73 95% CI]). Conclusion: SQ and NoH yielded comparable utility to SHFM for one-year survival prediction among advanced HF patients, are easy-to-use and could inform bedside decision-making.